Artemether-Lumefantrine Combination Therapy for Treatment of Uncomplicated Malaria: The Potential for Complex Interactions with Antiretroviral Drugs in HIV-Infected Individuals. (6th April 2011) - Byakika-Kibwika, Pauline; Lamorde, Mohammed; Mayanja-Kizza, Harriet; Khoo, Saye; Merry, Concepta; Van geertruyden, Jean-Pierre
Abstract : Treatment of malaria in HIV-infected individuals receiving antiretroviral therapy (ART) poses significant challenges. Artemether-lumefantrine (AL) is one of the artemisisnin-based combination therapies recommended for treatment of malaria. The drug combination is highly efficacious against sensitive and multidrug resistant falciparum malaria. Both artemether and lumefantrine are metabolized by hepatic cytochrome P450 (CYP450) enzymes which metabolize the protease inhibitors (PIs) and nonnucleoside reverse transcriptase inhibitors (NNRTIs) used for HIV treatment. Coadministration of NNRTIs and PIs with AL could potentially cause complex pharmacokinetic drug interactions. NNRTI by inducing CYP450 3A4 enzyme and PIs by inhibiting CYP450 3A4 enzymes could influence both artemether and lumefantrine concentrations and their active metabolites dihydroartemisinin and desbutyl-lumefantrine, predisposing patients to poor treatment response, toxicity, and risk for development of resistance. There are scanty data on these interactions and their consequences. Pharmacokinetic studies to evaluate these interactions in the target populations are urgently needed.